IMPACT OF THE LUMBAR STIFFNESS RELATED TO ARTHRODESIS TO FUNCTIONAL DISABILITY - Ramos,Camila Maribondo Medeiros (2021)
ABSTRACT Objective: To assess the impact of stiffness associated with lumbar spinal fusion on disability and quality of life. Methods: This is a retrospective study including 40 patients (mean age: 57.7 ± 16.2) who underwent spinal surgery with fusion including the lumbar segment and a minimum of 24-month postoperative follow-up. The version translated and adapted to Portuguese of the Lumbar Stiffness Disability Index (LSDI) questionnaire was applied to assess the disability associated with stiffness secondary to lumbar spinal fusion. To quantify postoperative clinical lumbar stiffness / mobility, the Modified-Modified Schober Test (MMST) was applied. Results: There was a moderate negative correlation (r = -0.320), but significant (p = 0.04), between the MMST value and the LSDI score. The average of LSDI score in patients with extension of spinal fusion to the sacrum was higher than in patients without extension to the sacrum (p = 0.002), indicating greater disability in those with extension to the sacrum. Conclusions: In patients undergoing lumbar spinal fusion, the disability related to lumbar stiffness, measured by the LSDI score, was directly related to clinical lumbar stiffness, measured by the modified-modified Schöber test. The inclusion of the sacrum in fusion showed an association with worsening of disability related to lumbar stiffness. Level of evidence III; Retrospective analysis.